FUS regulates autophagy by mediating the transcription of genes critical to the autophagosome formation. Issue 3 (18th January 2021) - Arenas, Alexandra; Kuang, Lisha; Zhang, Jiayu; Kingren, Meagan S.; Zhu, Haining
Abstract: Fused in sarcoma (FUS) is a ubiquitously expressed RNA/DNA‐binding protein that plays different roles in the cell. FUS pathology has been reported in neurodegenerative diseases amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Mutations in FUS have also been linked to a subset of familial ALS. FUS is mainly localized in the nucleus although it shuttles between the nucleus and the cytoplasm. ALS‐linked mutations cause the accumulation of the FUS protein in cytoplasm where it forms stress granule‐like inclusions. The protein‐ and RNA‐containing inclusions are reported to be positive of autophagosome markers and degraded by the autophagy pathway. However, the role of FUS in the autophagy pathway remains to be better understood. Using immunoblot and confocal imaging techniques in this study, we found that FUS knockout (KO) cells showed a decreased basal autophagy level. Rapamycin and bafilomycin A1 treatment showed that FUS KO cells were not able to initiate autophagy as efficiently as wild‐type cells, suggesting that the autophagosome formation is affected in the absence of FUS. Moreover, using immunoblot and quantitative PCR techniques, we found that the mRNA and protein levels of the genes critical in the initial steps of the autophagy pathway (FIP200, ATG16L1 and ATG12) were significantly lower in FUS KO cells. Re‐expressing FUS in the KO cells restored the expression of FIP200 and ATG16L1. Our findings demonstrate a novel role of FUS in the autophagy pathway, that is, regulating the transcription of genes involved in early stages of autophagy such as the initiation and elongation of autophagosomes. Abstract : Fused in Sarcoma (FUS) pathology has been reported in neurodegenerative diseases amyotrophic lateral sclerosis and frontotemporal dementia. This study is to determine the role of FUS in the autophagy pathway. We found that FUS knockout cells showed a decreased basal autophagy level. Moreover, the mRNA and protein levels of the genes critical in the initial steps of the autophagy pathway were significantly lower in FUS knockout cells. Re‐expressing FUS in the knockout cells restored the expression of autophagy genes. Our findings demonstrate a novel role of FUS in regulating the transcription of genes involved in the early stages of autophagy.